Theoretical basics of political axiology in the context of political and philosophical discourse - Жеребятнікова, І. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Genesis and the main periods of the development of political axiology in the limits of social and political knowledge are investigated. Basic directions of forming and analysis of the value components of political activity in different theoretical approaches and concepts are considered. The specifics of functioning of the political processes across the spectrum of axiological problems are determined.